Discussion of “The Role of Performance Measures in the Intertemporal Decisions of Business Unit Managers” - Van Der Stede, Wim A. (Contemporary Accounting Research, 2013)
This article is a discussion of, but mostly a further reflection on, the 2011 CAR Conference paper by Abernethy, Bouwens, and van Lent, “The Role of Performance Measures in the Intertemporal Decisions of Business Unit Managers” (this issue, henceforth ABvL). If I could have picked a title for my discussion article, I would have called it, “The Informational and Motivational Dimensions of Managerial Long-Term Orientation: Tackling Ignorance and Pressure,” for reasons that will become obvious as I develop my key points underpinning this discussion.